The Living Fiqh: Anatomy, Philosophical Formulation, and Scope of Study - Zelfeni Wimra; Yasrul Huda; Mahlil Bunaiya; Abdul Rahim Hakimi (Institut Agama Islam Negeri Batusangkar, 2023)
The living fiqh is derived from the living al-Quran and the living al-Hadith. It requires refining its formulation and methodological model as a contemporary socio-anthropological approach to fiqh. This article discusses the formulation of the concept of the living fiqh both deductively and inductively-abductively. The aim is to formulate and present this conception as a new approach or model of study and evaluation of fiqh practice in the contemporary era. The method used is abductive construction based on integrating fiqh into the behavior of its participants in various cultural clusters of Islamic society. The result found in this research is the formulation of the concept of The Living Fiqh as an explanation for society's acceptance of fiqh not only as knowledge but also as a practical guide in their lives. The implication is the availability of a sociological framework of fiqh that can explain the integration of fiqh in the daily life of Muslim communities spread across various models of cultural practices.